The Effect of Intra-Generational Differences on the Ego States of Millennial Leaders in Indian Software Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Each person has a favorite ego state which they exhibit the most, or prefer the most, depending on the situations they face and the people they interact with. People belonging to different generations react differently to different situations based on their states of ego. This paper has classified the millennial generation into Early millennial leaders (Y1) and Late millennial leaders (Y2) based on suitable findings from the literature. Further, this paper intends to explore whether Millennial generation leaders differ in ego states within their generation. The study is carried out in convenient sampling method by collecting responses from 489 Millennial leaders working in the Indian software industry. Ego State Questionnaire- Revised [ESQ-R] is utilized to survey the sample population and MANOVA is performed to assay the ego differences within the generation. It is found that the Early millennial leaders exhibited parent ego and adult ego states whereas the Late millennial leaders exhibited child ego state. Future studies can be conducted in multi-generational context and can include gender-specific research to probe whether ego states differ between males and females..